REGIONAL FEATURES OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP DEVELOPMENT BASED ON CLUSTERS (American Journal of Interdisciplinary Research and Development, 2024)
The most important direction in the development of our country’s economy is the development of industry, in which the development of the cotton textile industry is of particular importance. Because an important factor in the development of the cotton textile industry is the availability of raw materials and the necessary infrastructure. In particular, a significant part of the gross regional product of the Namangan region is produced by light industry enterprises.